Photonic waveguide to free-space Gaussian beam extreme mode converter. Issue 1 (December 2018) - Kim, Sangsik; Westly, Daron; Roxworthy, Brian; Li, Qing; Yulaev, Alexander; Srinivasan, Kartik; Aksyuk, Vladimir
Abstract Integration of photonic chips with millimeter-scale atomic, micromechanical, chemical, and biological systems can advance science and enable new miniaturized hybrid devices and technology. Optical interaction via small evanescent volumes restricts performance in applications such as gas spectroscopy, and a general ability to photonically access optical fields in large free-space volumes is desired. However, conventional inverse tapers and grating couplers do not directly scale to create wide, high-quality collimated beams for low-loss diffraction-free propagation over many millimeters in free space, necessitating additional bulky collimating optics and expensive alignment. Here, we develop an extreme mode converter, which is a compact planar photonic structure that efficiently couples a 300 nm × 250 nm silicon nitride high-index single-mode waveguide to a well-collimated near surface-normal Gaussian beam with an ≈160 µm waist, which corresponds to an increase in the modal area by a factor of >105 . The beam quality is thoroughly characterized, and propagation over 4 mm in free space and coupling back into a single-mode photonic waveguide with low loss via a separate identical mode converter is demonstrated. To achieve low phase error over a beam area that is >100× larger than that of a typical grating coupler, our approach separates the two-dimensional mode expansion into two sequential separately optimized stages, which create a fully expanded and well-collimated Gaussian slab mode before out-coupling it into free space. Developed at 780 nm for integration with chip-scale atomic vapor cell cavities, our design can be adapted for visible, telecommunication, or other wavelengths. The technique can be expanded to more arbitrary phase and intensity control of both large-diameter, free-space optical beams and wide photonic slab modes. Photonic chips: Converting the light A procedure for converting light beams between widely differing modes will help fulfill the potential of photonic chips - devices that use light for data processing rather than the electrical circuits of conventional microchips. Developing photonic chip technology requires reliable interconversion between the nanometer-scale light beams traveling within the chips and wider beams that can serve as useful output from or input to the devices. Vladimir Aksyuk and colleagues at the National Institute of Standards and Technology, in Gaithersburg, Maryland, USA, have developed a 'mode converter' that interconverts the light beams in a photonic chip and external beams that are more than 100, 000 times as wide. This reliable and precisely controlled interconversion should assist the development of wide range of applications for photonic chips, including their use in computation, optical analysis and military technologies.